Peningkatan Aktivitas dan Hasil Belajar Peserta Didik Materi Persamaan Kuadrat Melalui Pembelajaran Discovery Learning Kelas IX A SMP Negeri 2 Gubug Tahun 2019/2020 - Rudihastuti Rudihastuti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This research is classroom action research, this classroom action research will be carried out in 2 cycles, where each cycle consists of 3 meetings. Each cycle goes through a cycle process consisting of 4 stages, namely: Planning, Action Implementation, Observation, Reflection. This research was conducted at SMP Negeri 2 Gubug, the time of the research was in the odd semester of the 2019/2020 school year. With a research period of 3 months (July to September 2019). The research subjects were students in class IX A. The results showed that: 1) The application of discovery learning learning can increase learning activities in the first cycle on average is 59.93% to 71.80 in the second cycle. 2) can improve student learning outcomes in the first cycle an average of 75.38 to 80.58 in the second cycle. And the percentage of completeness in the first cycle was 73.08% to 92.31% in the second cycle. Thus, it can be concluded that discovery learning is learning. can improve the learning activities of students in SMP Negeri 2 Gubug. and improve mathematics learning outcomes at SMP Negeri 2 Gubug.